Planting density in two cultivars of castor in the south of Tocantins - Carvalho, Edmar (2010)
In order to improve the system of production of castor oil, you need to determine the density of plants. It was conducted an experiment in the Cariri, Tocantins-TO, at the Fazenda Coqueiro, using seeds of BRS Nordestina and BRS Paraguaçú to verify the effect of five planting densities (2.5; 3.12; 4.16; 6.25 and 12.5 thousand plants ha-1) on yield and agronomic characteristics of castor. The experiment was installed in February 2006 with all plants receiving the same fertilization independent of density (NPK 5-25-15). The experimental design was randomized blocks with four replications and treatments arranged in a 5 x 2 x 3, for analysis of grain yields and in a 5 x 2 for the other traits evaluated. The treatments resulted in the combination of five densities (distance between plants growing 2.00; 1.60; 1.20; 0.80 and 0.40 m) for the 2.5; 3.12; 4.16; 6.25 and 12.5 thousand plants per hectare respectively, two cultivars (BRS Nordestina and BRS Paraguaçú) and three crops of fruit on the following dates: 06/07/2006; 03/08/2006 and 19/09/2006. Among the populations, the highest productivity was 12.5 thousand plants ha-1 for both cultivars. The average yield for Nordestina was 1,048 kg ha-1, and Paraguaçú was 1,013 kg ha-1, demonstrating the productive potential in the region of Cariri in Tocantins.